Public Services and Organizational Behavior on Community Welfare in Makassar City: Social Capital as Mediator - Ansar Amir (Jurnal Administrasi Publik (Public Administration Journal), 2026)
The study aims to analyze the influence of public services and organizational behavior on community welfare, with social capital serving as a mediating variable. Despite extensive research on public services and community welfare, limited studies have examined the mediating role of social capital in local government contexts. This study employed a quantitative approach with an explanatory research design. Data were collected through a Likert-scale questionnaire administered to 280 public service users across 14 sub-districts in Makassar City. The data were analyzed using path analysis to examine direct and indirect relationships among variables. The findings reveal that public services have a positive and significant effect on both social capital and community welfare, whereas organizational behavior has a negative and significant effect. Social capital positively influences community welfare and mediates the relationship between public services, organizational behavior, and community welfare. This study contributes to the public administration literature by highlighting the strategic role of social capital in strengthening community welfare outcomes. The findings suggest that improving public service quality, organizational behavior, and social capital is essential for enhancing community welfare and supporting sustainable development.